Lack of supportive leadership behavior predicts suboptimal self-rated health independent of job strain after 10 years of follow-up: findings from the population-based MONICA/KORA study - Schmidt, Burkhard; Herr, Raphael M.; Jarczok, Marc N.; Baumert, Jens; Lukaschek, Karoline; Emeny, Rebecca T.; Ladwig, Karl-Heinz (International Archives of Occupational and Environmental Health, 2018)
Objectives: Emerging cross-sectional research has identified lack of supportive leadership behavior (SLB) as a risk factor for workforce health. However, prospective evidence is hitherto lacking. SLB denotes support in difficult situations, recognition and feedback on work tasks. This study aims to determine the effect of SLB on suboptimal self-rated health (SRH) after 10 years considering potential moderators such as ages, sex, occupation and job strain. Methods: The sample included 884 employed participants drawn from the population-based prospective MONICA/KORA Study. SLB, SRH, as well as job strain were assessed by questionnaire. Logistic regressions estimated odds ratios (ORs) and corresponding 95% confidence intervals (CIs) for the effect of SLB at baseline on suboptimal SRH at follow-up. Analyses were adjusted for age, gender, lifestyle (alcohol, smoking, physical activity), socioeconomic status as well as for SRH and job strain at baseline. Results: Lack of SLB was associated with suboptimal SRH at baseline [OR 2.00, (95% CI 1.19–3.46)] and at follow-up [OR 2.33, (95% CI 1.40–3.89)]. Additional adjustment for job strain did not substantially alter this association [OR 2.06, (95% CI 1.20–3.52)]. However, interactions between SLB and job strain as well as gender became evident, indicating moderating influences on the association between SLB and SRH. Conclusion: Lack of supportive leadership was associated with suboptimal SRH at 10 years’ follow-up in men, even if SRH at baseline and other risk factors were taken into account. This effect is likely to be moderated by job strain.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Cohort study; Leadership; Self-rated health; Work stress; Workforce